Effect of two groups of scrotal circumference on the sexual performance and their correlation in Boer bucks - N. S., Mariani; S., Shanmugavelu; D., Yusof; W. M, Zahari; H, Yaakub (Malaysian Society of Animal Production, 2022)
The study was conducted at the Goat Farm, Biotechnology Centre of DVSS Keningau, Sabah, to determine the effect of two groups of scrotal circumferences on sexual performance and the correlation between scrotal circumference and sexual performance in Boer bucks. Ten healthy Boer bucks aged 1.5 years with an average body weight of 61.15?1.87 kg were randomly selected. They were divided into two groups according to their scrotal circumference. The scrotal circumference between 25 to 28 cm was grouped as G-I (n=5), while G-II (n=5) consisted of the scrotal circumference between 29 to 32 cm. Bucks were fed with commercial pellets and Napier grass according to the farm's routine practice. Data on the scrotal circumference and sexual performance, including latency to the first mount, number of mounts, latency to the first ejaculation, refractory period, number of ejaculations, and mating efficiency, were collected every two weeks for five consecutive weeks. Results indicated that Boer bucks with a scrotal circumference between 29 to 32 cm improved their sexual performance; the number of mounts significantly decreased (P<0.05), and the number of ejaculations and mating efficiency significantly increased (P<0.05) compared to the Boer bucks with a scrotal circumference between 25 to 28 cm. A high correlation was reported between scrotal circumference and the number of mounts (r= ?0.476, P<0.01), while scrotal circumference correlated with mating efficiency (r = 0.323, P<0.05). In conclusion, scrotal circumference between 29 to 32 cm can influence the sexual performance of Boer bucks.